Recent developments in side scan sonar techniques - Flemming, B. W.,Russell-Cargill, W. G. A.,Klein, M.,Denbigh, P. N. (Selbstverl., 1982)
Ohne Kurzreferat
Literaturangaben
Keywords: Side Scan Sonar; Geomorphologie